DEVELOPING ALTERNATIVE MATHEMATICS LEARNING MEDIA USE MATHEMATICA 8.0 OF INTEGRAL APPLICATION TO CALCULATE VOLUME OF SOLID OF REVOLUTION SUBJECT - Allim Setia Nugraha; Sugiyarto Sugiyarto (Universitas Ahmad Dahlan, 2017)
Learning mathematics in schools is still considered difficult and less enjoyable by the student. It needs to develop media that can support the learning of mathematics in schools. This study aims to plan, create and determine the feasibility study of the mathematics learning media of integral application to calculate the volume of solid of revolution subject. This research used the Research and Development (R & D) method. The step taken is a preliminary study, media development, validation by subject matter experts and media experts as well as due diligence by the user to obtain the final product in the form of media that is packaged with a CD. Collecting data used interview techniques, documents, and questionnaires. The instruments used in the data collection questionnaire tested by means of qualitative analysis. A data-processing technique used is quantitative descriptive. The results of this study in the form of media are packaged with a CD (Compact Disc). Stage of development of media produced is (1) a preliminary study; (2) development includes the study of the criteria of competence, media creation and validation by media experts and subject experts; (3) feasibility test of teaching media. To determine the feasibility of the media the test done in two stages. The result of phase I is 88.38% and phase II is 81.17%. The data-processing of the trial is concluded that instructional media created with the category of very suitable.